2022
DOI: 10.1186/s12885-022-10184-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between cancer stem cell gene expression signatures and prognosis in head and neck squamous cell carcinoma

Abstract: Background Various cancer stem cell (CSC) biomarkers and the genes encoding them in head and neck squamous cell carcinoma (HNSCC) have been identified and evaluated. However, the validity of these factors in the prognosis of HNSCC has been questioned and remains unclear. In this study, we examined the clinical significance of CSC biomarker genes in HNSCC, using five publicly available HNSCC cohorts. Methods To predict the prognosis of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…BMI1 was revealed to be a prognostic indicator for brain tumors, lung adenocarcinoma, gastric cancer, renal cell carcinoma, colorectal cancer, and ovarian cancer [ 22 ]. Kim et al showed that BMI1 was one of the four cancer stem cell-related genes in head and neck SCC that were associated with patient prognosis [ 23 ]. More relevantly, Kurihara et al revealed that the protein and mRNA expression of BMI1 occurred during the invasion of patients with tongue SCC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMI1 was revealed to be a prognostic indicator for brain tumors, lung adenocarcinoma, gastric cancer, renal cell carcinoma, colorectal cancer, and ovarian cancer [ 22 ]. Kim et al showed that BMI1 was one of the four cancer stem cell-related genes in head and neck SCC that were associated with patient prognosis [ 23 ]. More relevantly, Kurihara et al revealed that the protein and mRNA expression of BMI1 occurred during the invasion of patients with tongue SCC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of high-yield, next generation sequencing panels to cluster tumors into even more distinct subtypes based on immunogenomics has also been described ( 110 , 111 ). Others have suggested that expression of cancer stem cell markers in HPV-positive oropharyngeal squamous may help further characterize biological behavior and identify patients who derive the most benefit from de-escalation ( 112 ). Indeed, attempts to discern gene profile signatures that might be useful for risk stratification continue to be explored ( 113 ).…”
Section: De-escalation: Next Stepsmentioning
confidence: 99%